2019
DOI: 10.3389/fimmu.2019.00694
|View full text |Cite
|
Sign up to set email alerts
|

Activated Mesenchymal Stromal Cells Process and Present Antigens Regulating Adaptive Immunity

Abstract: Mesenchymal stromal cells (MSCs) are inherently immunomodulatory through production of inhibiting soluble factors and expression of immunosuppressive cell surface markers. We tested whether activated MSCs qualify for the induction of antigen-specific immune regulation. Bone marrow derived human MSCs were activated by interferon-γ and analyzed for antigen uptake and processing and immune regulatory features including phenotype, immunosuppressive capacity, and metabolic activity. To assess whether activated MSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 46 publications
(66 reference statements)
2
51
0
Order By: Relevance
“…Both fetal and maternal cells express HLA-ABC and the co-stimulatory molecule CD95, which could confer the low antigen-presenting properties observed. Moreover, it was reported that IFN-γ stimulation augments the expression of HLA-ABC, HLA-DR, and CD40 in hAMSC [84], and the expression of these immunogenic markers could be responsible for their stimulatory activities, as observed for MSC from other sources [85,86].…”
Section: Discussionmentioning
confidence: 93%
“…Both fetal and maternal cells express HLA-ABC and the co-stimulatory molecule CD95, which could confer the low antigen-presenting properties observed. Moreover, it was reported that IFN-γ stimulation augments the expression of HLA-ABC, HLA-DR, and CD40 in hAMSC [84], and the expression of these immunogenic markers could be responsible for their stimulatory activities, as observed for MSC from other sources [85,86].…”
Section: Discussionmentioning
confidence: 93%
“…Other immunomodulatory observations upon IFN-γ licensing of antigen-pulsed MSCs are also recorded (van Megen et al, 2019). For example, IFN-γ treatment is associated with the upregulation of B7-H1 (PD-L1) (Krampera et al, 2006).…”
Section: Conclusion and Future Recommendationsmentioning
confidence: 94%
“…Importantly, the study also shows that despite their IFN-γ-induced antigen presentation, MSCs inhibit autoreactive T-cells, an observation associated with PD-L1 upregulation and IDO secretion (Figure 1). The inhibitory effect even lasted beyond the removal of MSCs and the introduction of activation signals (antigen-pulsed DCs) (van Megen et al, 2019). However, in another report, IFNγ-induced upregulation of PD-L1 on antigen-presenting MSCs is believed to be tied to T-cell induction rather than inhibition (Stagg et al, 2006).…”
Section: Cancer Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies reported that MSCs may express these molecules and lose their hypoimmunogenic/immune privileged state. For example, treatment with interferon gamma (IFNγ), which represents an inflammatory environment, induces the expression of MHC class II molecules and increases the expression of MHC class I molecules (Romieu-Mourez et al, 2007;Van Megen et al, 2019).…”
Section: The Immunological Profile Of Mscsmentioning
confidence: 99%